Association between physical activity, physical fitness and stress with bone mineral density of elderly: a narrative review - Cabral, Rejane Maria Cruvinel; Oliveira-Silva, Iransé; Melo, Gislane Ferreira de (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Introduction: Aging is a physiological process that decreases muscle, skeletal and autonomic capacity, which increases the likelihood of developing chronic diseases. In addition to these losses, stress can be an aggravating factor to senescence and may be indirectly identified by increased cortisol. Researches indicates that a good amount of daily physical activity and adequate levels of physical fitness can minimize age-related losses and minimize the impact on bone mineral density (BMD). Objective: to present how the level of physical activity, physical fitness and stress are associated with elderly people’s BMD. Methods: Pubmed and Medline databases were searched for scientific articles in Portuguese and English. The descriptors were: Stress, Physical Activity, Physical Fitness, Elderly and Bone Mineral Density. The research and the study of the scientific articles were carried out from October to December 2018. Conclusion: The level of moderate physical activity improves physical fitness and increases BMD. While high levels of cortisol contribute to decreased BMD.